On the accuracy of Gaussian approximation to the distribution of sum of independent identically distributed random variables - Bikelis, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Бикялис. О точности аппроксимации распределений сумм независимых одинаково распределенных случайных величин нормальным распределением A. Bikelis. Apie nepriklausomų vienodai pasiskirsčiusių atsitiktinių dydžių pasiskirstymo aproksimavimo tikslumą normaliniu pasiskirstymu